Presupposition Analysis of Parhata in Batak Toba Wedding Ceremony - Luita Maria Amanda; Anna Riana Suryanti Tambunan (Universitas Negeri Medan, 2022)
This research aims were to describe the types of presupposition used by the Parhata in Batak Toba wedding ceremony and to reveal the realization of presupposition in Parhata’s spoken words in Batak Toba wedding ceremony based on Yule’s framework (2000). In this study the researcher adapted textual analysis (Mc Kee, 2013) to analyze the data. The sources of the data were two videos of wedding ceremonies of Batak Toba. The data were taken from the script of Parhata’s spoken words during the wedding ceremonies. The current research findings showed that the existential presupposition was dominantly used in Parhata’s spoken words. As the mediator and informant in the wedding ceremony, Parhata tended to utter in positive statements. The realization of presupposition types in Parhata’s utterances was recognized according to the theme of presupposition in Yule’s framework. Moreover, the six types of presupposition found in the current research although the findings from wedding ceremony video one and wedding ceremony video two as following; 40 existential presuppositions, five factive presuppositions, two non-factive presuppositions, four lexical presuppositions, one structural presupposition and two counterfactual presuppositions. The realization of presupposition types in Parhata’s utterances was identified by the characteristics of each presupposition, such as mentioning an entity or stating contrary to the fact.